1997
DOI: 10.1017/s0016756897006626
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Iapetus subduction under Irish Avalonia

Abstract: The Dowery Hill Member of metamorphosed basalt, dolerite and siltstone is here recognized as the oldest exposed volcanic unit of the Lower Ordovician Ribband Group, with a minimum age of early Arenig. Peperites and resedimented hydroclastic breccia demonstrate a volcanic origin for the basalts. The igneous rocks are tholeiitic, with a trace element geochemistry indicative of a subduction-modified fertile mantle source, which we interpret as recording an early stage of volcanic arc evolution. The member is ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…There has been wide acceptance that pre-Silurian southern Ireland represents part of Avalonia (e.g. Van der Voo 1983Voo , 1988Livermore et al 1985;Pickering et al 1988;Ford et al 1992;Cocks et al 1997;McConnell & Morris 1997;Keppie et al 2003;Tyrrell et al 2007;Fullea et al 2014;Todd 2015), but others have suggested linkages to different peri-Gondwanan domains. One school of thought contends that southern Ireland, Wales and southern England formed part of a number of terranes that collectively formed Cadomia (e.g.…”
Section: Regional Geology and Review Of Terranes In The British Islesmentioning
confidence: 99%
“…There has been wide acceptance that pre-Silurian southern Ireland represents part of Avalonia (e.g. Van der Voo 1983Voo , 1988Livermore et al 1985;Pickering et al 1988;Ford et al 1992;Cocks et al 1997;McConnell & Morris 1997;Keppie et al 2003;Tyrrell et al 2007;Fullea et al 2014;Todd 2015), but others have suggested linkages to different peri-Gondwanan domains. One school of thought contends that southern Ireland, Wales and southern England formed part of a number of terranes that collectively formed Cadomia (e.g.…”
Section: Regional Geology and Review Of Terranes In The British Islesmentioning
confidence: 99%
“…Within this sector of the orogenic belt (Fig. 2) tectonic and magmatic processes involved the accretion of predominantly Ordovician and Silurian turbidite and volcaniclastic sediments (Morris 1987; McConnell & Morris 1997).…”
Section: Geophysical and Geological Backgroundmentioning
confidence: 99%
“…According to currently applied plate tectonic reconstructions (e.g. McKerrow & Cocks 1995), Ordovician to Devonian magmatic activity in south-east Ireland originated in the same tectonic environment as the Lake District and East Anglia, although McConnell & Morris (1997) mention that the exact relationship between south-east Ireland and the Lake District has yet to be clarified. Also in the Brabant Massif there was some magmatic activity during Early Palaeozoic times (e.g.…”
Section: Regional Settingmentioning
confidence: 99%